A study on graphene reinforced carbon fiber epoxy composites: Investigation of electrical, flexural, and dynamic mechanical properties - Kaftelen-Odabasi, Hulya; Odabasi, Akin; ozdemir, Mustafa; Baydogan, Murat (Wiley, 2023)
In this study, graphene nanoplatelets (GNPs) added to epoxy matrix composite reinforced by aeronautical grade carbon fibers (CFs) were fabricated by the vacuum infusion method, and the effect of different GNPs contents (0.05, 0.25, and 1.25 wt%) on electrical conductivity, flexural properties, and dynamic mechanical properties were investigated. The results revealed an 8- and 73-times improvement in conductivity values across the thickness with the addition of 0.05 and 0.25 wt% GNPs, respectively, compared to the neat composite. Flexural test results showed that with the addition of 0.05 GNP, only 6% increase in flexural strength was obtained, while with the addition of 0.25 wt% GNP flexural strength remained almost the same as for the neat composite. On the contrary, the addition of GNPs (1.25% by weight) causes a reduction in the flexural strength with respect to the neat composite. This was confirmed by the fractured surfaces examined by scanning electron microscope which reveals that considerable amount of fiber-matrix debonding was observed with 1.25 GNPs loading. Dynamic mechanical analysis (DMA) revealed that the storage modulus of the neat composite increased by 12.6% with the addition of only a small amount of GNP (0.05% wt) compared to the neat composite. Composite with 1.25 GNP shows upward bending, affecting the shape of the cole-cole plot obtained from DMA results, indicating inappropriate interactions of GNPs in both the matrix and CF in the composite.
Keywords: CFRP; dynamic mechanical analysis; electrical conductivity; flexural properties; GNPs